Spot evaluation of dosimetry compliance amongst diagnostic radiology staff in a medical facility - Selemela, Letlhogonolo Patrick (My University, 2018)
INTRODUCTION It is important for radiation workers to wear a dosimeter while working in a radiology department as part of their daily practice. This is one of the requirements for radiation control set by the Department of Health (DoH). Dosimeters are used for monitoring the amount of radiation received by radiation workers while at work. AIM The aim of this study was to assess compliance with the wearing and correct placing of radiation dosimeters by radiation workers in four medical facilities. METHOD A prospective descriptive study was performed in the radiology departments of the Helen Joseph Hospital (HJH), Chris Hani Baragwanath Academic Hospital (CHBAH), Rahima Moosa Mother and Child Hospital (RHM), and Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Radiology staff workers were interviewed on an individual basis to determine whether they were wearing their dosimeter badge, and if so, whether they were wearing it in the correct manner. Unannounced spot checks and interviews were done on a random day. Data were collected in the general X-ray, computed-tomography (CT), fluoroscopy, and mammography units of each of the hospitals concerned. RESULTS Of the 85 participants, almost half (49.41%) did not have their dosimeter while working in their usual work environment. Of those who had their dosimeter on their person, 38% were wearing their dosimeter on either their collar or their chest pocket. In the sample, 25% of the consultant radiologists, 56% of the qualified radiographers, 41% of the radiology registrars and 83% of the radiographer students were wearing their dosimeter while at work. Sixty-seven per cent of the participants under the age of 32 were wearing their dosimeter, while only 30% of the participants between the ages of 33 and 65 had their dosimeter at work. 6 CONCLUSIONS As shown by this study, there was a low level of dosimeter compliance among senior radiographers and radiologists, and a non-existent level of compliance among nursing staff, working in the radiology departments concerned. The study highlighted a need for the introduction of targeted work-related educational and reinforcement programmes that would improve the knowledge and increase the awareness of radiation safety of all staff working in radiology departments.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology (MMed Rad.D) Johannesburg, 2018.
Keywords: Radiation Dosimeters; Radiation Dosimeters; Radiology